An Inconvenient Past of World War II in the Historical Policy of the Republic of Croatia - A. M. Ponamareva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
Historical research has always, to one degree or another, been used for political expediency, during the periods of war and intense social and political upheaval transforming into the ‘heavy artillery’ of the state propaganda. In recent years, this trend has received a powerful impetus, prompting scholars to critically reassess the role of historical memory in the formation of collective identities and political myths. These studies have already turned into a full-fledged independent research area, focused on politics of history and memory and the use of the past for political purposes in general. This paper examines the key features and content of the historical policy of the Republic of Croatia regarding its ‘inconvenient past’ of the World War II. While the experience of the recent Serbo-Croatian conflict is often glossed over, the landmark events of the 1940s are constantly invoked in the public rhetoric of the country’s leaders, turning into a ‘past that does not pass’. In the countries of the former Yugoslavia competing narratives are constructed around certain historical events and personalities: if Serbia concentrates on such topics as Jasenovac and anti-fascism, Croatia invokes the memories of the so-called Bleiburg massacre of 1945, the ‘Way of the Cross’ and the victims of communism. Jasenovac and Bleiburg are counterposed to each other as ‘places of remembrance’, which provide political opponents with yet another opportunity to challenge each other over differences in the interpretation of both the events of World War II and the contemporary bilateral relations. The author considers Serbo-Croatian dispute over historical events from the standpoint of the theory of stigmatization by E. Goffman. Within this theoretical framework, the author attempts to conceptualize the events of World War II as a special ‘stigma’ of Croatia. Such extrapolation is perfectly defensible on the grounds of the Erving Goffman’s classic theory. It allows for the identification of the type of strategy to promote the country’s reputation, chosen by the Republic of Croatia from those available to states with a ‘tarnished’ national identity. Building on the E. Goffman’s theory the author concludes that Croatia adopts the strategy of ‘selective amnesia’, preferring to conceal the controversial episodes of its history. The paper identifies methods of historical self-legitimation of the Republic of Croatia, as well as their foreign policy implications.